Simultaneous live-imaging of peroxisomes and the ER in plant cells suggests contiguity but no luminal continuity between the two organelles - Barton, Kiah A.; Mathur, Neeta; Mathur, Jaideep (Frontiers in Physiology, 2013)
Transmission electron micrographs of peroxisomes in diverse organisms, including plants, suggest a close association and even luminal connectivity with the endoplasmic reticulum (ER). After several decades of debate de novo peroxisome biogenesis from the ER is strongly favored in yeasts and mammals. Unfortunately many of the proteins whose transit through the ER constitutes a major evidence for peroxisome biogenesis from the ER do not exhibit a similar localization in plants. Consequently, at best the ER acts as a membrane source for peroxisome in plants. However, in addition to de novo biogenesis from the ER an increase in peroxisome numbers also occurs through fission of existing peroxisomes. In recent years live-imaging has been used to visualize peroxisomes and the ER but the precise spatio-temporal relationship between the two organelles has not been well explored in plants. Here we present our assessment of the peroxisome-ER relationship through imaging of living Arabidopsis thaliana plants simultaneously expressing different colour combinations of fluorescent proteins targeted to both organelles. Our observations on double transgenic wild type and a drp3a/apm1 mutant Arabidopsis plants suggest strong correlations between the dynamic behaviour of peroxisomes and their neighbouring ER. Although peroxisomes and ER are closely aligned there appears to be no luminal continuity between the two. Similarly, differentially coloured elongated peroxisomes of a drp3a mutant expressing a photoconvertible peroxisomal matrix protein are unable to fuse and share luminal protein despite considerable intermingling. Substantiation of our observations is suggested through 3D iso-surface rendering of image stacks, which shows closed ended peroxisomes enmeshed among ER tubules possibly through membrane contact sites. Our observations support the idea that increase in peroxisome numbers in plant cells occurs mainly through the fission of existing peroxisomes in an ER aided manner.